Kontribusi Perilaku Konsumen Terhadap Keputusan Pembelian Produk Shampo Sunsilk pada PT. Unilever Indonesia Tbk - Anjar Nawang (Lembaga Intelektual Muda (LIM) Maluku, 2022)
The purpose of this study was to determine the contribution of consumer behavior to the decision to purchase Sunsilk shampoo products. This research was conducted by distributing questionnaires to S1 students of Prof. Dr. Moestopo University (Beragama) in 2012-2013. This study used the correlation method and the Likert Scale conducted on 40 respondents. The variables in this study are about consumer behavior towards consumer purchasing decisions of Sunslik shampoo products as many as 46 respondents, random sampling, where sampling is such that each unit of the population has the opportunity to be selected as a sample. Data collection techniques use field research, namely interviews and questionnaires. Data processing techniques were obtained from the results of the distribution of questionnaires measured using the Likert Scale and calculated with the SPSS 17.0 for Windows program. The contribution of consumer behavior to consumer purchasing decisions of Sunsilk shampoo products from the results of research and calculations conducted by the author can be proven using simple regression analysis calculations, correlation coefficients and determinations. So each increase and decrease in the relationship of consumer behavior is offset by the correlation coefficient obtained r is 0.955 less than 1 (one). This shows that there is a weak and positive contribution between consumer behavior and consumer purchasing decisions